Human footprint - Maltby, Clive; Vargas, Elizabeth (Washington, D.C. : National Geographic, 2008)
Explores the amount of waste produced, resources consumed, and how much impact a person has on the Earth in the average lifetime.
Features: behind-the-scenes footage.
Host: Elizabeth Vargas.
Originally broadcast on television in 2008.
DVD, Dolby digital stereo.
Closed-captioned.
Keywords: Nature -- Effect of human beings on; Human ecology; Video recordings for the hearing impaired; Documentary television programs; Nonfiction television programs; Television programs